Adsorption and diffusion of alkali‐atoms (Li, Na, and K) on BeN dual doped graphene. Issue 11 (12th January 2019) - Ullah, Saif; Denis, Pablo A.; Sato, Fernando
Abstract: We employ first‐principles DFT calculations to explore the potential use of BeN dual doped graphene (DDG) as an anode material for alkali‐based batteries. The introduction of BeN in graphene raise the adsorption of Li, Na, and K by 1.37 eV (2.23 times), 1.23 eV (2.83 times), and 1.14 eV (2.14 times), respectively. Furthermore, BeN DDG offers a modest energy barrier for alkali atoms studied. Moreover, the alkali atoms have good chemistry with Be and the interaction strength decreases during the migration toward N. Most importantly, the exceptional storage capacity of BeN DDG for Li (~2255 mAh/g), Na (~996 mAh/g), and K (~747 mAh/g) makes it a highly desirable anode material. Additionally, the average open circuit voltage offered for Li (0.66 V), Na (0.33 V), and (K = 1.10 V) is found to be in excellent range. All these outstanding properties provide the possibility of using BeN DDG in future alkali‐based batteries. Abstract : Dual doped graphene (DDG), which results in the simultaneous integration of two dopants in graphene, represents an efficient tool to reduce the toxicity of Be to allow its wider‐use application. The interaction of Li/Na/K with BeN DDG is studied with the help of density functional theory. BeN DDG exhibits exceptional electrochemical properties. These results suggest that BeN DDG can serve as a promising anode material in alkali‐based batteries.